Cellular Ingestible DNA Nanostructures for Biomedical Applications. Issue 1 (8th January 2023) - Xu, Rui; Li, Yujie; Zhu, Chenyou; Liu, Dongsheng; Yang, Yuhe R.
Abstract : DNA Nanostructures In article number 2200119, Dongsheng Liu, Yuhe R. Yang, and co‐workers describe the development and construction of various cellular ingestible DNA nanostructures, summarize the loading strategies of functional substances, overview current biomedical applications, and finally discuss the remaining challenges and opportunities.